2022
DOI: 10.3390/antiox11091779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Temperature on Antioxidant and Heat Shock Protein Expression Profiles and Transcriptomic Responses in Crayfish (Cherax destructor)

Abstract: Low temperature is a critical factor restricting the growth and survival of aquatic animals, but research on the mechanism of response to low temperature in Cherax destructor is limited. C. destructor is one of the most important freshwater crustaceans with strong adaptability in Australia, and it has been commercialized gradually in recent years. Here, growth indicators, antioxidant parameters, anti-stress gene expression, and transcriptome sequencing were used on crayfish following 8 weeks of low-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
1
2
0
2
Order By: Relevance
“…In Yang,experiment, the expression of HSP60 and HSP70 was signi cantly upregulated, while other HSPs decreased or had no signi cant change at low temperatures in cray sh. His results indicated that HSP60 and HSP70 might have stronger protective effects at lowtemperature acclimation in C. destructor [33]. In our experiment, mRNA expression of most hsps showed a low level of decline under low salinity conditions, which was consistent with the experimental results of Bao et alTherefore, the hepatopancreas exhibit a sensitive HSPs response to promote immune process adaptation to salinity changes.These results suggest that the contribution of energy metabolism to osmotic regulation may lead to the decrease of HSP expression in gill of Apostichopus japonicus under low salinity stress.…”
Section: Discussionsupporting
confidence: 92%
“…In Yang,experiment, the expression of HSP60 and HSP70 was signi cantly upregulated, while other HSPs decreased or had no signi cant change at low temperatures in cray sh. His results indicated that HSP60 and HSP70 might have stronger protective effects at lowtemperature acclimation in C. destructor [33]. In our experiment, mRNA expression of most hsps showed a low level of decline under low salinity conditions, which was consistent with the experimental results of Bao et alTherefore, the hepatopancreas exhibit a sensitive HSPs response to promote immune process adaptation to salinity changes.These results suggest that the contribution of energy metabolism to osmotic regulation may lead to the decrease of HSP expression in gill of Apostichopus japonicus under low salinity stress.…”
Section: Discussionsupporting
confidence: 92%
“…Suhu merupakan parameter kunci dalam kualitas perairan karena dapat berdampak langsung terhadap metabolisme LAT dan dapat mempengaruhi kualitas perairan lain. Suhu juga dapat berpengaruh terhadap pertumbuhan dan molting pada krustase, termasuk LAT (Yang et al 2022). Dalam penelitian (Yang et al (2022) dan García-Guerrero et al (2013) diketahui bahwa suhu ideal bagi budidaya LAT adalah 25 -30 0 C, meskipun mereka tetap dapat bertahan pada suhu 23 -26 0 C.…”
Section: Suhuunclassified
“…Suhu juga dapat berpengaruh terhadap pertumbuhan dan molting pada krustase, termasuk LAT (Yang et al 2022). Dalam penelitian (Yang et al (2022) dan García-Guerrero et al (2013) diketahui bahwa suhu ideal bagi budidaya LAT adalah 25 -30 0 C, meskipun mereka tetap dapat bertahan pada suhu 23 -26 0 C.…”
Section: Suhuunclassified
“…Penaeus vannamei, commonly known as whiteleg shrimp, has become one of the most productive aquaculture species in the world due to its significant economic value [1]. Water temperature changes are common stressors in aquaculture; among these stressors, low temperature is a serious environmental stress factor [2][3][4]. Low temperatures can affect shrimp health by suppressing the immune system and disrupting physiological processes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%